Chemical components of the essential oils from leaf of Citrus sinensis (L.) Osbeck in Nghe An province - Thieu, Phan Xuan; Phu, Hoang Vinh; Dung, Nguyen Anh (Academia Journal of Biology, 2013)
The leaf oil of sweet orange (Citrus sinensis (L.) Osbeck), namely three culticars “Cam chanh”, “cam Chiu nhiet” and “cam Van du” in Nghe An province was obtained by steam distilation. The chemical components of essential oil were analyzed by gas chromatography (GC) and gas chromatography-mass spectrometry (GC/MS). The results showed that there were fourty eight components identified. In which, the principal components were monoterpene hydrocarbons. The main constituents of essential oil were found to be sabinene (24.85-34.45%), linalool (9.95-12.25%), limonene (7.13-9.80%), (Z)-b-ocimene (6.80-8.87%), ∆3-carene (3.08-4.07%), E-citral (geraniol) (6.99-10.66%), Z-citral (neral) (1.65-2.63%), b-caryophyllene (2.52-3.40%), spathoulenol (allo) (3.08-5.11%) and b - sinensal (4.20-6.75%).